Effectiveness of an Education Program on Nurses̕ Practices toward Preventing Central Venous Catheter Related Infection in Al-Nasiriya Hospitals - Khalida M Khader (Journal of Global Pharma Technology, 2016)
Background: Central venous catheters are routinely used in Intensive Care Units (ICU) to provide vascular access. They are used to access a large vessel (internal jugular, subclavian or femoral) to monitor central venous pressure (CVP), administer fluids, blood products, total parental nutrition (TPN), and medications. Patients in Intensive Care Units are at a higher risk for infection due to multiple factors such as age, severity of illness, and underlying disease conditions combined with a critical illness. So, educational programs concerning this essential subject can be of imperative benefit for both patient and nurse. Objective: To evaluate the effectiveness of an educational program on nursesꞌ practices toward preventing central venous catheter related infection in ICU.  Methodology: A quasi experimental study design is carried out at AL-Nasiriyah hospitals from 19th of October 2017 to the 6st of June 2018 and a probability (Random) sample of (60) nurses who have been working in the ICU .those nurses are divided into two groups, study and control groups, each group consisted of (30) nurses. To measure the effectiveness of nursing educational program through the use of practice checklist includes (46) items concerning preventing central venous catheter related infection in ICU. Reliability of instrument was determined through the use of test and retest and the instrument validity was determined through a panel of (14) experts. Results: The results showed a positive effectiveness of educational program. It also shows that there are highly significant differences in the study group between pre and post-tests at significance level P ≤ 0.05. Conclusion: The study concluded that the nurses working at ICU have the minimum level of experience in preventing central venous catheter related infection and need educational program and sessions. Recommendation: The study recommended that providing an educational program should be ongoing for nurses to enhance their skills about the preventing central venous catheter related infection.Keywords: Effectiveness, Education Program, Nursesꞌ Practices, Prevention, Central Venous Catheter, Infection.